2015
DOI: 10.1037/rep0000036
|View full text |Cite
|
Sign up to set email alerts
|

The association of negative attributions with irritation and anger after brain injury.

Abstract: These preliminary findings suggest that irritation and anger after TBI may be linked to the negative attributions they make about others' behaviors. Findings further indicate a relationship between negative attributions and trait aggression. Thus, individuals with TBI who have higher trait aggression may have a tendency to make more negative attributions about others' behaviors, and in turn, have stronger feelings of irritation and anger as a response. Future studies with healthy controls and larger sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
(81 reference statements)
2
33
1
Order By: Relevance
“…This is inconsistent with a study by Neumann et al (2015), which indicated that the more TBI patients perceived other people's behaviors as intentional, hostile, or blameworthy, the more irritated and angry they felt. Even though Neumann et al (2015) examined judgments of scenarios not facial expressions, it would be expected that the misattribution Behaviors of Concern after Acquired Brain Injury of anger to facial expressions would also be related to irritation and anger and in turn to more aggression. On the other hand, there may be differential contributions of the severity of brain injury and other factors, such as post-traumatic disorder (PTSD), to anger and aggression.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This is inconsistent with a study by Neumann et al (2015), which indicated that the more TBI patients perceived other people's behaviors as intentional, hostile, or blameworthy, the more irritated and angry they felt. Even though Neumann et al (2015) examined judgments of scenarios not facial expressions, it would be expected that the misattribution Behaviors of Concern after Acquired Brain Injury of anger to facial expressions would also be related to irritation and anger and in turn to more aggression. On the other hand, there may be differential contributions of the severity of brain injury and other factors, such as post-traumatic disorder (PTSD), to anger and aggression.…”
Section: Discussioncontrasting
confidence: 79%
“…The tendency to make attributions that are significantly more negative than the attributions of the general population is termed negative attribution bias. Negative attribution bias is a clinical problem that has been found in TBI patients (Neumann, Malec, & Hammond, 2015). A negative attribution bias is also found to be related to interpersonal dysfunction (Carton, Kessler, & Pape, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…47 This standardized measure has been widely used in many populations, including TBI. 4,[49][50][51][52][53] Toronto Alexithymia Scale (TAS-20) 28,54 : The TAS-20 is a 20-item questionnaire that measures total alexithymia, and three subconstructs: difficulty identifying feelings (emotional self-awareness), difficulty describing feelings, and externally-oriented thinking. Scores range between 20-100; scores of 51 or less indicate low alexithymia; scores of 61 and higher indicate high alexithymia; scores in between indicate moderate alexithymia.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely acknowledged that problems with aggression are quite common after traumatic brain injury (TBI) 1 , with studies documenting aggression rates between 12% and 45% [2][3][4][5][6] . While the prevalence of post-TBI aggression compared to that of healthy controls has been less studied, findings from two studies suggest that it is more pervasive in the TBI population.…”
mentioning
confidence: 99%
“…6,7 The roots of posttraumatic anger are complex and vary across individuals. Pre-injury personality characteristics, direct injury to frontal/executive systems that modulate affect and behavior, 8 and cognitive deficits affecting communication and inference in social situations 9 may all play a role. In addition, limitations in financial and personal independence and loss of meaningful activity can compound frustration.…”
Section: Introductionmentioning
confidence: 99%